Determinants of tourism demand in spain: A European perspective from 2000-2020 - Susana Borrego-Domínguez; Fernando Isla Castillo; Mercedes Rodríguez-Fernández (Economies, 2022)
This empirical study evaluates European tourism demand in Spain from 2000 to 2020. To test the hypotheses, we have modelled tourism demand, which is measured in terms of travellers arriving in Spain. An Error Correction Model adapted to a panel structure has been utilised to work within a time series context and differentiate up to 14 European countries of origin. The findings denote that over the short and the long term, gross domestic product (GDP) and the number of beds positively relate to tourism demand. Still, the stock market indices are not significant in both terms. The price index, trade flows, and length of stay differ in the short and the long term. Results of this study call the attention of policy makers and the private sector to encourage an increase in the supply of available beds to ensure post-pandemic sustainability.
Keywords: 330; Europe; GDP; panel data; stock market indices; supply of beds; tourism demand